Organizational Culture and Employee Performance in Post-Covid-19: Does Employee Engagement Mediate in the Model? - Dhyan Parashakti, Ryani; Ekhsan, Muhamad; Nursaputra, Tedy (KnE Social Sciences, 2023)
This study examines the relationship between organizational culture and employee performance in the post-Covid-19 era, with a focus on determining whether employee engagement mediates in the model. The research aims to understand the impact of the pandemic on organizational culture and employee performance, and the role that employee engagement plays in this relationship. Data were collected through surveys and analyzed using statistical techniques to identify patterns and relationships. Data was analyzed using the Smart PLS software version 3.0. The findings of this study will provide insights for organizations on how to effectively manage their culture and performance in the post-Covid-19 era. Furthermore, this research will contribute to the existing literature on the topic by exploring the post-Covid-19 context and the potential mediating role of employee engagement. Overall, the study aims to provide practical recommendations for organizations on how to create a positive culture and enhance employee performance in the post-Covid-19 era. Keywords: organizational culture, employee engagement, employee performance, post Covid